The Bases as Turning Point - Magno, Alexander R. (Kasarinlan: Philippine Journal of Third World Studies, 2008)
1989 is marked as one of the crucial times in Philippine political history. On 18 September 1991, the Military Bases Agreement (MBA) between the US and the Philippines is set to expire. Whether the Philippine Senate, acting on the interest of the Filipino, would give a new lease of life to the US military facilities here in the country or not is the center of this article’s analysis. Drawing its inputs from the political situation at that time, this article discusses the repercussion of allowing the US military bases to stay here and the non renewal of the Military Bases Agreement juxtaposed to the political actors involved and in a broader sense, our country’s future such a decision entails.
Keywords: Military Bases Agreement; Legislative-Executive Bases Council